The responses of microbial extracellular enzyme activities to soil sample storage conditions across different soil types - Panpan Liu; Jiacong Zhou; Chris Freeman; Mallavarapu Megharaj; Kyungjin Min; Linchuan Fang; Gangsheng Wang; Lars Elsgaard; Nicolas Fanin; Hojeong Kang; Taiki Mori; Jianwei Li; et al. (Soil Ecology Letters, 2026)

Long-term P management has limited impacts on soil microbial communities, with unique patterns driven by location, land use, and soil depth - Kirill Bogdanov; Parag Bhople; Giulia Bondi; Naoise Nunan; Lars Elsgaard; Anke M. Herrmann; Karl G. Richards; Mart Ros; David Wall; Fiona Brennan; Sergio E. Morales; Timothy J. Clough (Applied Soil Ecology, 2026)

Ten-year effects of perennial cropping systems on soil organic carbon stock and stability in sandy soils: Mechanisms and biochemical drivers - Mingming Zong; Diego Abalos; Ji Chen; Zhi Liang; Yue Li; Lars Elsgaard; Christopher Poeplau; Marcus Schiedung; Uffe Jørgensen (European Journal of Agronomy, 2025)

Impact of liming and maize residues on N2O and N2 fluxes in agricultural soils: an incubation study - Lisa Pfülb; Lars Elsgaard; Peter Dörsch; Roland Fuß; Reinhard Well (Biology and Fertility of Soils, 2025)
Since it is known that nitrous oxide (N 2 O) production and consumption pathways are affected by soil pH, optimising the pH of agricultural soils can be an important approach to reduce N 2 O emissions. Because liming effects on N 2 O reduction had not been studied under ambient atmosphere and typical bulk density of arable soils, we conducted mesoscale incubation experiments with soils from two liming trials to investigate the impact of long-term pH management and fresh liming on N transformations and N 2 O production. Soils differed in texture and covered a range of pH levels (3.8–6.7), consisting of non-limed controls, long-term field-limed calcite and dolomite treatments, and freshly limed soils. Both soils were amended with 15 N-labelled potassium nitrate (KNO 3 ) and incubated with and without incorporated maize litter. Packed soil mesocosms were cycled through four phases of alternating temperatures and soil moistures for at least 40 days. Emissions of N 2 O and dinitrogen (N 2 ) as well as the product ratio of denitrification N 2 O/(N 2 O + N 2 ), referred to as N 2 Oi were measured with the 15 N gas flux method in N 2 -reduced atmosphere. Emissions of N 2 O increased in response to typical denitrifying conditions (high moisture and presence of litter). Increased temperature and soil moisture stimulated microbial activity and triggered denitrification as judged from 15 NO 3 − pool derived N 2 O + N 2 emissions. Fresh liming increased denitrification in the sandy soil up to 3-fold but reduced denitrification in the loamy soil by 80%. N 2 Oi decreased throughout the incubation in response to fresh liming from 0.5–0.8 to 0.3–0.4, while field-limed soils had smaller N 2 Oi (0.1–0.3) than unlimed controls (0.9) irrespective of incubation conditions. Our study shows that the denitrification response (i.e., N 2 O + N 2 production) to liming is soil dependent, whereas liming effects on N 2 Oi are consistent for both long- and short-term pH management. This extends previous results from anoxic slurry incubation studies by showing that soil pH management by liming has a good mitigation potential for agricultural N 2 O emissions from denitrification under wet conditions outside of cropping season.

Importance of sampling frequency for the observed dynamics of SOC content in the Danish long-term monitoring network - Laura Sofie Harbo; Rojina Lama; Camilla Lemming; Lars Elsgaard (Geoderma Regional, 2025)

Diversified crop rotations improve soil microbial communities and functions in a six-year field experiment - Yifei Sun; Xiaolin Yang; Lars Elsgaard; Taisheng Du; Kadambot H.M. Siddique; Shaozhong Kang; Klaus Butterbach-Bahl (Journal of Environmental Management, 2024)

Corrigendum to “Liming effects on microbial carbon use efficiency and its potential consequences for soil organic carbon stocks” [Soil Biol. Biochem. 191 109342] - Julia Schroeder; Claudia Dǎmǎtîrcǎ; Tobias Bölscher; Claire Chenu; Lars Elsgaard; Christoph C. Tebbe; Laura Skadell; Christopher Poeplau (Soil Biology and Biochemistry, 2024)

Response to Čapek and Šantrůčková’s comment to “Liming effects on microbial carbon use efficiency and its potential consequences for soil organic carbon stocks” [Soil Bio. Biochem. 194: 109437] - Julia Schroeder; Claudia Dǎmǎtîrcǎ; Tobias Bölscher; Claire Chenu; Lars Elsgaard; Christoph C. Tebbe; Laura Skadell; Christopher Poeplau (Soil Biology and Biochemistry, 2024)

Liming effects on microbial carbon use efficiency and its potential consequences for soil organic carbon stocks - Julia Schroeder; Claudia Dǎmǎtîrcǎ; Tobias Bölscher; Claire Chenu; Lars Elsgaard; Christoph C. Tebbe; Laura Skadell; Christopher Poeplau (Soil Biology and Biochemistry, 2024)

Evaluation of the relation between soil biomass of arbuscular mycorrhizal fungi and glomalin-related soil protein in conservation agriculture - Stamatios Thomopoulos; Lars Elsgaard; Lars Juhl Munkholm; Sabine Ravnskov (Soil Biology and Biochemistry, 2023)

Priming effects decrease with the quantity of cover crop residues – Potential implications for soil carbon sequestration - Zhi Liang; Jim Rasmussen; Christopher Poeplau; Lars Elsgaard (Soil Biology and Biochemistry, 2023)

Nonlinear effects of biochar on greenhouse gas emissions and soil microbial community composition under intensive vegetable production in South China - Yige Liu; Mengxuan Shi; Zonghai Chen; Zijie Tang; Jiayu Tan; Jihui Tian; Lars Elsgaard; Ying Lu; Bo Li (Applied Soil Ecology, 2023)

Long‐term nitrogen loading alleviates phosphorus limitation in terrestrial ecosystems - Ji Chen; Kees J. van Groenigen; Bruce A. Hungate; César Terrer; Jan‐Willem van Groenigen; Fernando T. Maestre; Samantha C. Ying; Yiqi Luo; Uffe Jørgensen; Robert L. Sinsabaugh; Jørgen E. Olesen; Lars Elsgaard (Global Change Biology, 2020)
Increased human‐derived nitrogen (N) deposition to terrestrial ecosystems has resulted in widespread phosphorus (P) limitation of net primary productivity. However, it remains unclear if and how N‐induced P limitation varies over time. Soil extracellular phosphatases catalyze the hydrolysis of P from soil organic matter, an important adaptive mechanism for ecosystems to cope with N‐induced P limitation. Here we show, using a meta‐analysis of 140 studies and 668 observations worldwide, that N stimulation of soil phosphatase activity diminishes over time. Whereas short‐term N loading (≤5 years) significantly increased soil phosphatase activity by 28%, long‐term N loading had no significant effect. Nitrogen loading did not affect soil available P and total P content in either short‐ or long‐term studies. Together, these results suggest that N‐induced P limitation in ecosystems is alleviated in the long‐term through the initial stimulation of soil phosphatase activity, thereby securing P supply to support plant growth. Our results suggest that increases in terrestrial carbon uptake due to ongoing anthropogenic N loading may be greater than previously thought.

Soil carbon loss with warming: New evidence from carbon‐degrading enzymes - Ji Chen; Lars Elsgaard; Kees Jan van Groenigen; Jørgen E. Olesen; Zhi Liang; Yu Jiang; Poul E. Lærke; Yuefang Zhang; Yiqi Luo; Bruce A. Hungate; Robert L. Sinsabaugh; Uffe Jørgensen (Global Change Biology, 2020)
Climate warming affects soil carbon (C) dynamics, with possible serious consequences for soil C stocks and atmospheric CO 2 concentrations. However, the mechanisms underlying changes in soil C storage are not well understood, hampering long‐term predictions of climate C‐feedbacks. The activity of the extracellular enzymes ligninase and cellulase can be used to track changes in the predominant C sources of soil microbes and can thus provide mechanistic insights into soil C loss pathways. Here we show, using meta‐analysis, that reductions in soil C stocks with warming are associated with increased ratios of ligninase to cellulase activity. Furthermore, whereas long‐term (≥5 years) warming reduced the soil recalcitrant C pool by 14%, short‐term warming had no significant effect. Together, these results suggest that warming stimulates microbial utilization of recalcitrant C pools, possibly exacerbating long‐term climate‐C feedbacks.

Fertilizer-induced fluxes dominate annual N2O emissions from a nitrogen-rich temperate fen rewetted for paludiculture - Tanka P. Kandel; Sandhya Karki; Lars Elsgaard; Poul Erik Lærke (Nutrient Cycling in Agroecosystems, 2019)

Carbon mineralization and microbial activity in agricultural topsoil and subsoil as regulated by root nitrogen and recalcitrant carbon concentrations - Zhi Liang; Lars Elsgaard; Mette Haubjerg Nicolaisen; Annemette Lyhne-Kjærbye; Jørgen Eivind Olesen (Plant and Soil, 2018)

Soil Properties Control Glyphosate Sorption in Soils Amended with Birch Wood Biochar - K. G. I. D. Kumari; Per Moldrup; Marcos Paradelo; Lars Elsgaard; Lis W. de Jonge (Water, Air, & Soil Pollution, 2016)

Endospores, prokaryotes, and microbial indicators in arable soils from three long-term experiments - Paulina Tamez-Hidalgo; Bent T. Christensen; Mark A. Lever; Lars Elsgaard; Bente Aa. Lomstein (Biology and Fertility of Soils, 2016)

Full GHG balance of a drained fen peatland cropped to spring barley and reed canary grass using comparative assessment of CO2 fluxes - Sandhya Karki; Lars Elsgaard; Tanka P. Kandel; Poul Erik Lærke (Environmental Monitoring and Assessment, 2015)

Mitigation of greenhouse gas emissions from reed canary grass in paludiculture: effect of groundwater level - Sandhya Karki; Lars Elsgaard; Joachim Audet; Poul Erik Lærke (Plant and Soil, 2014)

Effect of biochar on aerobic processes, enzyme activity, and crop yields in two sandy loam soils - Zhencai Sun; Esben Wilson Bruun; Emmanuel Arthur; Lis Wollesen de Jonge; Per Moldrup; Henrik Hauggaard-Nielsen; Lars Elsgaard (Biology and Fertility of Soils, 2014)

Biomass Yield and Greenhouse Gas Emissions from a Drained Fen Peatland Cultivated with Reed Canary Grass under Different Harvest and Fertilizer Regimes - Tanka P. Kandel; Lars Elsgaard; Sandhya Karki; Poul E. Lærke (BioEnergy Research, 2013)

Dynamics of mineral nitrogen, water-soluble carbon and potential nitrification in band-steamed arable soil - Lars Elsgaard (Biology and Fertility of Soils, 2010)

Heterogeneity of bacterial populations and pesticide degradation potentials in the unsaturated zone of loamy and sandy soils - Finn Vinther; Lars Elsgaard; Ole Jacobsen (Biology and Fertility of Soils, 2001)

Rubber stoppers used with sulphidic media: a note of caution - Lars Elsgaard (World Journal of Microbiology and Biotechnology, 2000)

Microbial ethylene consumption in peat-soil during ethylene exposure of Begonia elatior - Lars Elsgaard; Lise Andersen (Plant and Soil, 1998)